Vai trò của thống kê và những vấn đề đặt ra đối với hoạt động thống kê trong quản lý các cơ quan thư viện-thông tin - Nguyễn, Thị Lan Thanh (Cục Thông tin khoa học và công nghệ quốc gia, 2023)
Underlines the role of statistics and cognition in managing library and information activities; discuss some reasons affecting effectiveness of statistical activity in library and information institutions; sets forth some requirements and solutions to enhance effectiveness of statistical activity in these institutions.